Implementasi Program Rehabilitasi Sosial Rumah Tidak Layak Huni dalam Peningkatan Kualitas Hunian Masyarakat Berpenghasilan Rendah Pada Kelurahan Rungkut Kidul Kota Surabaya - Zildjianisa Rhisma Widyatna; Diana Hertati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Social rehabilitation of uninhabitable houses aims to restore social function and improve the quality of housing for the poor through improving the condition of the house and/or environmental infrastructure, either in whole or in part, by applying the spirit of mutual cooperation, togetherness and social values. the value of social solidarity in society. This research examines the implementation of the Social Rehabilitation Program for Uninhabitable Houses (RS-Rutilahu) in Rungkut Kidul Village, Surabaya City, with a focus on improving the quality of housing for low-income communities through collaboration between the government and the community. The aim of this research is to determine the implementation of the RS-Rutilahu program in improving the quality of housing for low-income communities in Rungkut Kidul Village. Based on David C. Korten's program implementation theory, this research examines three main aspects: the program itself, the implementing organization, and the beneficiaries. The research results show that this program has succeeded in achieving the house improvement target, but there are still obstacles related to community participation and strict administrative requirements. It is hoped that these findings can become a reference for increasing program effectiveness in the future. Social rehabilitation of uninhabitable houses aims to restore social function and improve the quality of housing for the poor through improving the condition of the house and/or environmental infrastructure, either in whole or in part, by applying the spirit of mutual cooperation, togetherness and social values. the value of social solidarity in society. This research examines the implementation of the Social Rehabilitation Program for Uninhabitable Houses (RS-Rutilahu) in Rungkut Kidul Village, Surabaya City, with a focus on improving the quality of housing for low-income communities through collaboration between the government and the community. The aim of this research is to determine the implementation of the RS-Rutilahu program in improving the quality of housing for low-income communities in Rungkut Kidul Village. Based on David C. Korten's program implementation theory, this research examines three main aspects: the program itself, the implementing organization, and the beneficiaries. The research results show that this program has succeeded in achieving the house improvement target, but there are still obstacles related to community participation and strict administrative requirements. It is hoped that these findings can become a reference for increasing program effectiveness in the future.